Investment multiplier effect expands tourism destinations: Community of economy and social in Jungjungan Village, Ubud Bali - Suryanata, I Gusti Ngurah Putra (International research journal of management, IT and social sciences, 2019)
The study is aimed at discussing the investment multiplier effect expands tourism destinations. The main problem is how can multiplier investments in the tourism sector minimize unemployment in Junjungan Village, Ubud, Bali. The results of the analysis and discussion show that the existence of investments influences many of the social and economic life of the community, because there are so many benefits or benefits obtained by both the Gianyar government and the local community as an integral part of the tourism business on the island, both in the form of tax and assistance provided to local communities to improve the quality of life and also training in the human resources. The more investment in this village, it is expected to be able to open as wide employment opportunities as possible. Therefore, unemployment is minimized and public income is expected to continue increasing.